ASSOCIATIONS BETWEEN BMI, PHYSICAL FUNCTION AND BONE HEALTH IN COMMUNITY DWELLING OLD ADULTS. (11th November 2018) - Chang Gudjonsson, M; Geirsdottir, O; Jonsson, P; Thorsdottir, I; Ramel, A
Abstract: Background: High body mass index (BMI) is a risk factor for good health but the results are contradictory in late life. The associations between BMI, physical function and bone health were investigated in a group of apparently healthy, physically active, community dwelling old adults. Methods: This was a cross-sectional study including 236 community dwelling old people (age range: 65–92 years, 58.2% female). Bone mineral density (DXA), timed-up-and-go (TUG), six-minute-walk-for-distance (6MWD), anthropometrics, quadriceps strength and clinical blood variables were assessed. Results: Mean age was 73.7 ± 5.7 years. According to linear models corrected for age, smoking and gender, higher obesity was related to lower quadriceps strength relative to body weight, to lower physical function, i.e., lower gait speed and longer TUG time, as well as to lower 25OHD but to higher PTH. Of the participants, only 1% of men and 4% of women had osteoporosis, the corresponding numbers for osteopenia were 35% and 45%. Obesity was related to high bone mineral density (T-score) in femur, lumbar and total. Conclusions: In this highly functional cohort of old adults, obesity was related to poorer strength and less physical function in older adults which should make obese individuals more prone for falls and fractures. However, although obesity was also related to a poorer hormonal profile, obesity was related to higher BMD. Future studies need to determine the net effects of higher BMI and fall and fracture risk of obese elderly.